Online-only learning during the COVID19 pandemic. What determines accounting students’ engagement? - Joanna Krasodomska; Ewelina Zarzycka; Anna Mazurczak-Mąka; Monika TUREK-RADWAN (Zeszyty Teoretyczne Rachunkowości, 2022)
Objective: The paper aims to identify the factors that determine accounting students’ engagement in online-only learning during the COVID-19 pandemic. Methodology/research approach: The unified theory of acceptance and use of technology (UTAUT) is used as a theoretical lens. Survey responses provided by accounting students participating in online-only courses at Polish universities between May and June 2020 are analyzed, and regression analysis is employed to verify the research hypotheses. Findings: According to our findings, student effort expectancy and performance signifi-cantly and positively influence their engagement in online-only learning. Age is also significant for student engagement, with younger students being more engaged in online-only learning than older ones. Originality/value: The study contributes to the literature on distance learning as it investigates a relatively unexplored group of students in an unprecedented situation. The paper also proposes new measures to capture UTAUT factors. The findings are also relevant for practice. It seems that after the pandemic, online learning will continue to be used and ensuring student engagement will become more relevant than technological issues, already mastered by both sides of the educational process.